Pengaruh Penggunaan Teknologi dalam Pembelajaran Terhadap Prestasi Belajar di Sekolah Luar Biasa Al Khariq - Indah Wulandari; Nova Estu Harsiwi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research aims to identify what learning technologies are used as learning media that can be used by students who have special needs. The use of technology in learning in Special Schools (SLB) is increasingly important in facing the development of modern education. This research aims to explore the influence of the use of technology on student learning achievement in the Special School (SLB) environment. The research method used is a quantitative study by collecting research materials and processing the research. The results of the research show that the use of technology in learning has a significant positive impact on student learning achievement at SLB Al-Khariq Dsn Tempel-Ngonggot-Nganjuk. The experimental group showed greater improvements in academic achievement compared to the control group. In addition, data analysis also revealed that students felt more involved and motivated in the learning process when technology was used effectively. These findings indicate the importance of appropriate technology integration in the context of inclusive education to improve the quality of learning and academic outcomes of students in Special Schools (SLB). This research makes an important contribution in supporting inclusive education policies and practices that center on the use of technology to improve the learning achievement of special school students. The implications of these findings can help policy makers and educational practitioners to design more effective and inclusive learning strategies in special school environments.